Design and Synthesis of 2, 2′‐Diindolylmethanes to Selectively Target Certain G‐Quadruplex DNA Structures. Issue 37 (9th August 2016) - Livendahl, Madeleine; Jamroskovic, Jan; Ivanova, Svetlana; Demirel, Peter; Sabouri, Nasim; Chorell, Erik
Abstract: G‐quadruplex (G4) structures carry vital biological functions, and compounds that selectively target certain G4 structures have both therapeutic potential and value as research tools. Along this line, 2, 2′‐diindolylmethanes have been designed and synthesized in this work based on the condensation of 3, 6‐ or 3, 7‐disubstituted indoles with aldehydes. The developed class of compounds efficiently stabilizes G4 structures without inducing conformational changes in such structures. Furthermore, the 2, 2′‐diindolylmethanes target certain G4 structures more efficiently than others and this G4 selectivity can be altered by chemical modifications of the compounds. Abstract : G‐quadruplex selectivity : 2, 2′‐Diindolylmethanes have been designed and synthesized. The compounds specifically stabilize defined G‐quadruplex structures without inducing large conformational changes, and the observed selectivity can be fine‐tuned by chemical modifications.